2020
DOI: 10.1017/psrm.2020.50
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two peoples: motivated reasoning in the aftermath of the Brexit Vote

Abstract: Partisanship is a powerful driver of economic perceptions. Yet we know less about whether other political divisions may lead to similar evaluative biases. In this paper, we explore how the salient divide between “Remainers” and “Leavers” in the UK in the aftermath of the Brexit referendum has given rise to biased economic perceptions. In line with the cognitive dissonance framework, we argue that salient non-partisan divisions can change economic perceptions by triggering processes of self- and in-group justif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…In the case of likely Remain voters, the average treatment effect is both comparatively small and also statistically indistinguishable from zero (β = .04 |p = 0.426). As Sorace and Hobolt (2020) demonstrate in the case of economic evaluations, we therefore observe that Brexit-based orientations exhibit a partisanshiplike motivated reasoning effect when it comes to forming evaluations of trust in the government in the face of incumbent opportunism.…”
Section: Figure 3: Moderating Effectssupporting
confidence: 56%
See 1 more Smart Citation
“…In the case of likely Remain voters, the average treatment effect is both comparatively small and also statistically indistinguishable from zero (β = .04 |p = 0.426). As Sorace and Hobolt (2020) demonstrate in the case of economic evaluations, we therefore observe that Brexit-based orientations exhibit a partisanshiplike motivated reasoning effect when it comes to forming evaluations of trust in the government in the face of incumbent opportunism.…”
Section: Figure 3: Moderating Effectssupporting
confidence: 56%
“…The effect of snap elections on political trust will be moderated by ideological congruence with the incumbent In the specific case of the UK under consideration in this study, research highlights the emergence of salient Brexit-based political identities in addition to party identities following the 2016 Brexit referendum (Hobolt, Leeper and Tilley, 2020). Importantly, these Brexit-based identities -whether one identifies as a pro-EU "Remainer" or an anti-EU "Leaver" -have also been found to exhibit partisan-like moderating effects on the responsiveness to political and economic information (Sorace and Hobolt, 2020).…”
Section: H2amentioning
confidence: 84%
“…Consider the "Leave" versus "Remain" divide over Brexit that began to consume British politics in 2015. Hobolt and her colleagues note the traditional view of affective polarization as pertaining to animosity directed at members of the opposing party, but showed that identification with a stance on Brexit, which cut across party lines, generated affective polarization and outgroup prejudice that were at least as strong as those associated with partisanship (Hobolt, Leeper, & Tilley, 2020;Sorace & Hobolt, 2020; see also Evans and Schaffner, 2019). A similar phenomenon occurred with the Tea Party movement in American politics in 2010.…”
Section: Social Identification With Political Groups As a Source Of Belief-system Structurementioning
confidence: 99%
“…Recent research, however, demonstrates that voters make systematic errors in evaluating economic performance and attributing responsibility for economic conditions, both because of cognitive constraints – such as the availability heuristic (Bartels, 2008; Kramer, 1971) – and because of group-serving bias (Bartels, 2002; Bisgaard, 2015; Enns et al, 2012; Evans and Pickup, 2010; Evans and Andersen, 2006; Sorace and Hobolt, 2020; Tilley and Hobolt, 2011). This calls into question the assumption that economic performance is easily observable and ‘digested’ by voters.…”
Section: Introductionmentioning
confidence: 99%
“…Different past performance indicators could be adopted to monitor political agents. Economic performance has been the indicator of choice in most studies of retrospective voting, but recent research has demonstrated that the processing of economic information is too complex for voters, and prone to cognitive biases (Bartels, 2002; Enns et al, 2012; Sorace and Hobolt, 2020). Moreover, economic performance is not an appropriate indicator for all types of elected representatives (Healy and Malhotra, 2013).…”
Section: Introductionmentioning
confidence: 99%